Emotional Dysregulation and Trauma Symptoms Mediate the Relationship Between Childhood Abuse and Nonsuicidal Self-Injury in Adolescents - Andersson, Hedvig; Aspeqvist, Erik; Dahlström, Örjan; Svedin, Carl Göran; Jonsson, Linda S.; Landberg, Åsa; Zetterqvist, Maria (Frontiers in Psychiatry, 2022)
Background: Nonsuicidal self-injury (NSSI) is common in adolescents. Emotion dysregulation has been identified as a core mechanism in the development and maintenance of NSSI and it is therefore an important target when addressing NSSI. The pathogenic connection between different kinds of childhood abuse, difficulties in emotion regulation and NSSI needs further investigation. The objective of this study was to examine whether difficulties with emotion regulation and trauma symptoms, separately and together, mediate the relationships between sexual, physical and emotional abuse and NSSI. Method: Cross-sectional data was collected from 3,169 adolescent high-school students aged 16-19 years (M = 18.12, SD = 0.45). Data from self-reported experiences of childhood abuse, current difficulties with emotion regulation (measured with the Difficulties with Emotion Regulation Scale, DERS-16) and trauma symptoms (measured with the Trauma Symptom Checklist for Children, TSCC), and NSSI were collected. Structural Equation Modeling (SEM) was used to test the proposed relationships between variables. Results: The prevalence of life-time NSSI was 27.4%. Prevalence of reported childhood abuse was 9.2%, 17.5%, 18.0% for sexual, physical and emotional abuse, respectively. Childhood abuse, difficulties with emotion regulation and trauma symptoms exhibited significant positive associations with NSSI in adolescents. Emotional dysregulation and trauma symptoms were both found to mediate the relationship between childhood abuse and NSSI. Latent variable models were found to fit data well. Conclusion: Results indicate that increased levels of emotional dysregulation and trauma symptoms in relation to childhood abuse contribute to the increased risk of NSSI. Further, results point to some aspects of emotional dysregulation and trauma symptoms being more important in this regard. Clinical implications are discussed.